(untitled) (PANGEEA, 2025)
Inconventional energy sources. Market trends and industry. Regional development was born of efforts both by economists and by those charged with planning the territory. Regional development policy has become one of the policies most important and most complex of the European Union, a status that stems from the fact that its aim, the European Union acts on some important areas for development, economic growth and the small and medium enterprises, transport, agriculture, urban development, environmental protection, employment and training, education, etc. The objective of traditional regional development policies is to reduce territorial disparities, achieving a relative balance between economic and social development levels of different regions of the national territory. Management phenomenon of regional development requires as a necessary condition of the affirmation of the phenomenon itself, to monitor its evolution and to ensure its resilience. Using renewable resources is considered one of the solutions for management of regional development, given that the question of exhaustion in a not too distant future of primary commodities and becoming their increasingly less accessible in terms of cost or processing required to obtain their costs no longer justified.